2022
DOI: 10.1001/jamanetworkopen.2021.48474
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Timing of Postpartum Intrauterine Device Insertion and Breastfeeding With Risks of Intrauterine Device Expulsion

Abstract: IMPORTANCE Intrauterine device (IUD) expulsion increases the risk of unintended pregnancy; how timing of postpartum IUD insertion and breastfeeding are associated with risk of expulsion is relevant to the benefit-risk profile. OBJECTIVE To evaluate the association of postpartum timing of IUD insertion and breastfeeding status with incidence and risk of IUD expulsion. DESIGN, SETTING, AND PARTICIPANTS The Association of Perforation and Expulsion ofIntrauterine Devices (APEX-IUD) cohort study included women aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…1,3,4,[6][7][8][9][10][11] The APEX-IUD (Association of Perforation and EXpulsion of Intra-Uterine Devices) study was an observational cohort study of 326,658 individuals designed to assess the association of breastfeeding and timing of postpartum IUD insertion with IUD expulsion and IUD-related uterine perforation among individuals in the United States. 12,13 The study also evaluated risks of IUD expulsion and uterine perforation in individuals with heavy menstrual bleeding and by IUD type (copper IUDs vs levonorgestrel-releasing intrauterine systems [LNG-IUDs]). 14,15 Although APEX-IUD was conducted to address a postmarketing requirement from the U.S. Food and Drug Administration, data from the study were also used to address questions raised by the European Medicines Agency about specific demographic, reproductive, and medical risk factors associated with IUD expulsion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,4,[6][7][8][9][10][11] The APEX-IUD (Association of Perforation and EXpulsion of Intra-Uterine Devices) study was an observational cohort study of 326,658 individuals designed to assess the association of breastfeeding and timing of postpartum IUD insertion with IUD expulsion and IUD-related uterine perforation among individuals in the United States. 12,13 The study also evaluated risks of IUD expulsion and uterine perforation in individuals with heavy menstrual bleeding and by IUD type (copper IUDs vs levonorgestrel-releasing intrauterine systems [LNG-IUDs]). 14,15 Although APEX-IUD was conducted to address a postmarketing requirement from the U.S. Food and Drug Administration, data from the study were also used to address questions raised by the European Medicines Agency about specific demographic, reproductive, and medical risk factors associated with IUD expulsion.…”
Section: Resultsmentioning
confidence: 99%
“…The APEX-IUD study population included individuals aged 50 years or younger at the time of IUD insertion and in the health care system for 12 months or longer before IUD insertion; only the first IUD insertion in the study period was included. To reduce the effects of confounding by breastfeeding or early postpartum timing at IUD insertion, 4 , 12 , 16 , 18 and the effect of pregnancy on BMI measurement, these analyses excluded individuals with a delivery 52 weeks or less before IUD insertion. Individuals were followed from IUD insertion until IUD expulsion, uterine perforation, removal, reinsertion, or expiration (ie, end of the approved duration of use); pregnancy; hysterectomy or other sterilization procedure; death; disenrollment from the health care system; or end of the study period (June 30, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that IUD placement between 2 to 4 weeks postpartum is associated with lower rates of expulsion than historical expulsion rates for immediate postpartum placement. Similarly, a retrospective cohort study demonstrated the highest expulsion rates among IUDs placed immediately postpartum (46.5/1000 person-years) and lower rates for IUDs placed between 4 days and 6 weeks postpartum (10.9/1000 person-years) and 6 to 14 weeks postpartum (9.3/1000 person-years) …”
Section: Discussionmentioning
confidence: 99%
“…7 Breastfeeding is associated with lower IUD expulsion risk. 8 Nulliparous and Adolescent Patients. LARC can be safely used in nulliparous and adolescent patients.…”
Section: Special Considerationsmentioning
confidence: 99%